Global health (security), immigration governance and Covid-19 in South(ern) Africa: An evolving research agenda - Jo Vearey; Thea de Gruchy; Nicholas Maple (Elsevier, 2021)
The Covid-19 pandemic provides a stark reminder of the political tensions associated with the field of immigration and health, highlighting the central role that nationalism, racism and xenophobia play in determining responses to communicable diseases. The blurring of global health, immigration governance, and the global health security agendas has long been recognised. However, an improved understanding of the politics influencing these entanglements, specifically within the context of the Covid-19 response in low- and middle-income country contexts, is urgently needed. This includes - but is not limited to - the immediate concerns surrounding inclusive social, political and medical responses to Covid-19; vaccine nationalism - at both global and national levels; and calls for 'vaccine passports'.To this end, we draw on the Southern African Development Community (SADC) context - one associated with high levels of diverse population movements and a large burden of communicable diseases - to explore responses to Covid-19. We unpack tensions surrounding the management of migration and the ways in which sovereignty impacts attempts at building regional, coordinated responses to migration and health, and consider how this affects progress towards global health targets. With an initial focus on South Africa, we build on previous work exploring the blurring of global health, immigration governance, and the global health security agendas in SADC, and draw from ongoing research on the governance of migration and health within the region. This includes current and evolving research exploring migration and Covid-19, initiated in March 2020 when the first cases of Covid-19 were identified in Southern Africa.The aim is for these findings to catalyse a new and evolving researh agenda to inform the development and implementation of appropriate pandemic responses in a region associated with some of the highest levels of inequality globally. To this end, an evolving research agenda should be responsive to current needs. We suggest that, in SADC, priority research should focus on improving our understanding of (1) the political factors influencing the (dis)connections between migration and health governance structures in the context of Covid-19, and how to overcome these in the context of a pandemic; and (2) the motivations for and implications of a 'vaccine passport' system on movement within and beyond the SADC region. This requires a reactive, cross-disciplinary, regional research network. In a context where funding for research is increasingly inaccessible, this requires innovative, informal, collaborative engagement.